Rheumatoid Arthritis Treatment After Methotrexate: The Durability of Triple Therapy Versus Etanercept. Issue 10 (6th September 2017) - Peper, Shana M.; Lew, Robert; Mikuls, Ted; Brophy, Mary; Rybin, Denis; Wu, Hongseng; O'Dell, James
Abstract : Objective: Although it is common for rheumatologists to initiate biologic agents after failure of methotrexate monotherapy in rheumatoid arthritis (RA), ample data support the initial use of combinations of conventional therapies in this clinical scenario. Our study explores the durability of triple therapy (methotrexate, sulfasalazine, and hydroxychloroquine) versus methotrexate‐etanercept in RA. Methods: RA patients with suboptimal response to methotrexate (n = 353) were randomized to either triple therapy or methotrexate‐etanercept therapy in a 48‐week, double‐blinded, noninferiority trial. Patients without clinical improvement at 24 weeks were switched to the alternative treatment. Of the total, 289 participated in followup. We report treatment durability, Disease Activity Score in 28 joints (DAS28), and other measures during an open‐label extension for an additional period up to 72 weeks. Results: Mean ± SD duration of open‐label followup was 11 ± 6 months. The likelihood of continuing conventional therapy at 1 year was 78% for triple therapy versus 63% for methotrexate‐etanercept, with most treatment changes occurring at the start of followup. More patients changed from methotrexate‐etanercept to triple therapy than from triple therapy to methotrexate‐etanercept ( P  = 0.005). DAS28 scores and other disease activity measures were not different for the 2 treatments and were stable during followup. Conclusion: In RA patients with suboptimal methotrexate response randomized to receive triple therapy or methotrexate‐etanercept, the former was found to be significantly more durable. Given cost differences and similar outcomes, the variable durability demonstrated provides additional evidence supporting conventional combinations over biologic agent combinations as the first choice after methotrexate inadequate response.